Critical Analysis of the Content of French Textbooks in the First and Second Year of Educational Guidance for Iranian Students from the Perspective of Language and Culture Education and Its Components - Hoda Khayat (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2020)
Using the descriptive-critical method and emphasizing the concept of language-culture education, in this paper, we have tried to find only two books from the series of French-language textbooks of education, namely French textbooks for the first and second year of middle school. The realization of the goals and needs of French language teaching should be reviewed. In this research, we examined the place of teaching culture and mother tongue (origin) and foreign language (destination) in these two books. The educational approach of these books is a semi-audio-visual approach, and due to scientific advances in the field of foreign language teaching, these educational books have not been able to keep pace with current knowledge and in line with today’s needs of teaching / learning French. Intercultural skills training is one of the important functions of the educational system. The aim of this study was to describe and critically analyze the content of French books in the seventh and eighth years of Intermediate 1 in terms of addressing the categories of language and culture education and interculturalism. There is still a fundamental weakness in the teaching of destination culture and interculturalism, and there is a need for greater coherence between the teaching of culture and mother tongue with the teaching of intercultural components.